Implementasi Kebijakan Program Kartu Indonesia Pintar di Sekolah Dasar Negeri 11 Bancah Kecamatan Koto Parik Gadang Diateh Kabupaten Solok Selatan - Putri Pesi; Dasman Lanin (PUBLICNESS: Journal of Public Administration studies, 2022)
From This study aims to analyze the implementation of the Program Kartu Indonesia Pintar (PIP) policy at SD Negeri 11 Bancah Kecamatan Koto Parik Gadang Diateh Kabupaten Solok South. Informants in this study were determined by purposive sampling method, where the selection of informants was based on certain characteristics. As for the technique of collecting data through a field research in the form of semi-structured interviews addressed to the Principal, BK teachers and parents of students. then observation and documentation study. The number of data sources consists of the Principal, Counseling Teacher and 4 parents of students. The research location was carried out at SDN 11 Bancah Kecamatan Koto Parik Gadang Diateh. The results of this study indicate that the implementation of the Program kartu Indonesia Pintar (PIP) at SD Negeri 11 Bancah Koto Parik Gadang Diateh has been going well. This can be seen from the variable implementation of the KIP policy that has met the target, because the determination of KIP recipient students is right and on target. Sufficient and competent human resources in running it, the characteristics have carried out responsibilities in accordance with the rules that have been set. The economic condition of parents whose income is insufficient, while the social environment for the participation and response of parents of students who are very enthusiastic about their children as KIP recipients